The Preparation of Skins and Clothing in the Eastern Canadian Arctic - T. H.; Manning, E. W. (Polar Record, 1944)
During the eight years I spent in the Arctic, I have experimented with a variety of clothing, but in neither winter nor summer have I found any more suitable than that worn by the present-day Eskimos in districts where caribou are still plentiful. From 1938 to 1941 we prepared all our own skins, and my wife made all the skin clothing excepting the seal-skin boots. The descriptions are primarily intended to give practical information on clothing to travellers in Arctic regions. For this reason we have made no attempt to discuss women's clothing. My wife adopted men's clothing because of its superior convenience, and because it requires less material. Women's clothing is made with a view both of being different from the men's and of accommodating the baby, always carried on the back. Except as otherwise indicated, both the clothing and the methods of preparation here described are those of the Eskimos of Baffin Island, Melville Peninsula, Southampton Island, and the coastal region from Repulse Bay to Chesterfield Inlet; and where mention is made of “the Eskimos”, the reference is to those of these regions only.